°Crisis? °qué crisis? : España en busca de su camino / Walther L. Bernecker, Diego Íįguez Hernández, Günther Maihold (eds.) - Bernecker, Walther L.Íįguez Hernández, DiegoMaihold, Günther (Bibliotheca Ibero-Americana; 130)
Incluye referencias bibliográficas